Strain rate effects on the compressive response of wood and energy absorption capabilities – Part B: Experimental investigation under rigid lateral confinement. (15th November 2018) - Wouts, J.; Haugou, G.; Oudjene, M.; Morvan, H.; Coutellier, D.
Abstract: The compressive properties of spruce and beech wood species at a large range of strain rates – from 0.001 to 600  s - 1 – under rigid lateral confinement have been investigated, using an original experimental device especially developed for the purpose. The work is motivated by the need to explore the dynamic behavior of wood up to large strains close to 70%. Three experimental apparatus have been used to obtain the compressive responses: the quasi-static tests have been performed using a Sintech 20D test system, the compressive responses at intermediate strain rates have been obtained with an Instron VHS65/20 apparatus and the dynamic tests have been conducted using a Split Hopkinson Pressure Bars (SHPB) system. The strain rate sensitivity of wood is clearly visible on the crushing strength with an increase between 80 and 155% but also on the plastic like behavior. In addition, the entire responses exhibit an elastic-plastic like behavior whereas an elastic brittle behavior could be observed, in the previous Part A which was focused on the compression configuration without lateral confinement. Even if no significant effect of the rigid lateral confinement is observed on the apparent Young modulus and the crushing strength values for both species, the wood energy absorption capability is better when longitudinal failure mechanisms are restricted thanks to the rigid lateral confinement.